A Facile Synthesis and Characterisation of Novel Mesoporous Bioactive Glass Nanoparticles/ Xylitol Based Biodegradable Polyester Composites For In Vitro Degradation Studies And Anti-Inflammatory Activity. (2019) - Deepa, K.; Jaisankar, V.
Abstract: Xylitol is a biocompatible polyol that has been used to make highly cross-linked polyester elastomers and dendrimers for medical applications such as wound healing, tissue engineering, bioimaging, orthopedic devices, implant coatings and drug delivery. The incorporation of mesoporous bioactive glass (MBG) nanoparticles in polymeric structure enhances the biocompatibility of the polymers. In the present study, poly (xylitol maleate suberate) and poly (xylitol citrate sebacate) copolyesters were synthesised by catalyst free melt polycondensation method. The MBG nanoparticles (SiO2 –CaO–P2 O5 ) was prepared through a novel sacrificial liquid template method by sol–gel process using ethyl acetate added in the cetyltrimethylammonium bromide (CTAB) aqueous solution to form micro-emulsion droplets as liquid template in which aqueous ammonia was added as template corrodent catalyst for hydrolysis. The polyester/ n-MBG composite was prepared by solution mixing method. The synthesized pre-polymers were characterized by solubility studies, FTIR, 1 H NMR and 13 C NMR spectral methods. The molecular weight (Mw) and polydispersity index were determined by Gel Permeation Chromatography (GPC). The glass transition (Tg) and melting temperature (Tm) of polymer and its nanocomposites were studied by Differential Scanning Calometry (DSC). The viscosity of the polyesters and tensile strength (Mpa), young's modulus (Mpa), elongation at break % of polymers and its nanocomposite were characterized by Rheometry and universal testing machine (UTM). In vitro degradation and swelling studies of the polyester were examined. The polymer nanocomposite thin film was characterised by XRD, HRSEM and EDX. The polymer and its nanocomposites were studied by anti-inflammatory activity. Thus, the prepared polymer and its nanocomposites may be a good candidate as therapeutic molecules carriers for bone and dental tissue regeneration.